ANALISIS PEMILIHAN MODA DENGAN REGRESI LOGISTIK PADA RENCANA KORIDOR TRAYEK TRANS SARBAGITA - Putu Widiarta, Ida Bagus; Wardana, I Gusti Ngurah (Jurnal Ilmiah Teknik Sipil, 2012)
High traffic flows on the main road has increased traffic problems such as traffic congestion. Public transport system, Trans Sarbagita, is expected to solve such problem. It is required therefore, to study on mode choices on the Trans Sarbagita corridor. The study objective is to analyze the socio-economic characteristics of Terminal Mengwi-Kota-Pelabuhan Benoa Route and to analyze the mode choice model. Analysis was conducted on primary data obtained by performing Home Interview Survey. Data were analyzed using logistic regression models and using SPSS version 16.0. Mode choice model was represented by probability of using Public Transportation to Private Transportation as follows: ln [P (AU) / P (AP)] = -2103 +2872 (BUKERJAR) + 1409 (DAPATBUL), with contributions of BUKERJAR and DAPATBUL is 23.78% and 37.66% respectively. The result of analysis is to provide recommendation or information about modal choice according to the needs of the residents for intra-and inter-zones movement.
Keywords: mode choice, logistic regression, Trans Sarbagita.